EP 24. Contralateral smiles induced by deep brain stimulation of the nucleus accumbens region in a patient with major depressive disorder. Issue 9 (September 2016) - Rasche, D.; Moll, C.K.; Brüggemann, N.; Zurowski, B.; Tronnier, V.
Abstract : Introduction: Deep brain stimulation (DBS) is a well-established procedure for the treatment of therapy-refractory movement disorders. Limited evidence suggests that DBS of the nucleus accumbens region (NACC) may be effective for the treatment of psychiatric disorders, such as obsessive compulsive disorder and major depressive disorder (MDD). Hitherto, little is known concerning behavioural responses upon acute high-frequency stimulation of the NACC region in patients suffering from MDD. Objective: To further characterize behavioural responses and clinical effects elicited upon acute unilateral DBS of the NACC area. Intra- and postoperative observations (including video-sequences) as well as a two-month outcome are presented. Material and Methods: We performed bilateral NACC-DBS in a female patient (age: 47) with MDD refractory to psycho-, pharmaco- and electroconvulsive (>50 sessions) therapy on a compassionate-use basis. The stereotactic procedure was performed under local anaesthesia. The NACC was targeted (x) 7 mm lateral to the midline, (y) 3 mm anterior to the anterior commissure, (z) 4 mm below the anterior commissure-posterior commissure plane. A commercially available DBS lead with 4 contacts (model 3391, Medtronic Co., MN, USA; contact length: 3 mm; interelectrode distance: 4 mm) was inserted bilaterally for permanent stimulation. Results: Upon test-stimulation in the operating room, acute unilateral NACC-DBS on both hemispheres stereotypically induced a visible facial reaction with a contralateral smile (bipolar stimulation of the ventralmost contacts (0− cathodal vs. 1+ anodal); pulse width: 90 μs; frequency: 130 Hz). This smile could repeatedly be elicited either when stimulation amplitude was slowly ramped up to 7 mA, or abruptly switched on to 4–5 mA. The smile was invariably associated with a significantly improved mood (as assessed by an analog scale). This effect was documented by different examiners and clearly reproducible in the subsequent clinical course. A dramatic improvement of the depression scores, patient's mood and social behaviour was documented at a first follow-up (6 weeks postoperatively). Conclusion: Albeit preliminary, the patient's beneficial response tentatively suggests that NACC-DBS may be a viable option for selected patients with MDD. In line with previous reports on stimulation-induced smile responses in patients with obsessive compulsive disorder, our intraoperative observations support and expand the notion of the NACC area constituting or containing an important interface between limbic and motor networks, respectively, that may be involved in the pathophysiology of MDD. It is suggested that the results of long-term NACC-DBS in patients with MDD should be evaluated by larger patient samples and randomized, controlled trials.